The evolution of digital health: a global, Latin American, and Brazilian bibliometric analysis - Vinadé Chagas, Maria Eulália; de Oliveira Laguna Silva, Gabriela; Ricardo Fernandes, Gabriel; Tizianel Aguilar, Gabriela; Motta Dias da Silva, Mariana; Moraes, Evandro Luis; D Avila Lottici, Isadora; da Rosa de Amorim, Jerusa; de Abreu, Tiago; de Campos Moreira, Taís; Cezar Cabral, Felipe (Frontiers in Digital Health, 2025)
IntroductionDigital health provides remote healthcare assistance, contributing to reducing inequalities in access to services. For its widespread adoption, it is essential to disseminate successful models implemented in countries with developed digital health networks, so that they can be adapted and replicated in developing regions. The dissemination of scientific studies on the topic, combining digital health activities within various contexts with scientific research, is crucial for promoting significant advancements in the understanding and application of these technologies. This study aims to conduct a comprehensive bibliometric analysis of global scientific production in digital health from 2019 to 2024, with special attention to Latin America and Brazil.MethodsA bibliometric analysis was conducted with searches in PubMed, Scopus, and Web of Science. The analysis used the Bibliometrix package in RStudio, and the data were filtered for the global dimension, Latin American countries, and Brazil. The authorship analysis was restricted to publications with at least one Brazilian author and was carried out through a manual check of each record. The protocol was registered on the Open Science Framework platform under the number 10.17605/OSF.IO/43WQ5.ResultsA total of 51,723 publications were included in the global dimension, 2,410 in Latin America, and 1,317 in the Brazilian analysis. The number of publications increased from 2019 to 2021. In the global scenario, the United States led scientific production in digital health, whereas Brazil led in Latin America.ConclusionDigital health has expanded exponentially, consolidating itself as a strategic pillar in healthcare systems. Investments in international collaborations that encourage knowledge exchange, strengthen research networks, and drive scientific publications are essential. These partnerships are crucial for adapting digital tools to different socioeconomic contexts and ensuring equitable care for the population.